2013
DOI: 10.1158/2326-6066.cir-13-0030
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-Derived Suppressor Cells Attenuate TH1 Development through IL-6 Production to Promote Tumor Progression

Abstract: Collaborative action between tumor cells and host-derived suppressor cells leads to peripheral tolerance of T cells to tumor antigens. Here, we showed that in tumor-bearing mice, generation of tumor antigen-specific effector T-helper cells (T H 1) was significantly attenuated, and impaired T H 1 differentiation was restored by the temporal blockade of interleukin (IL)-6 activity at the T-cell priming phase. Furthermore, we found that Gr-1 þ myeloid-derived suppressor cells (MDSC) served as a source of IL-6 in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 48 publications
3
68
0
Order By: Relevance
“…Although CD8 + T cells are important in tumor clearance, they are not the only cell involved 75 . MDSCs have been reported to have inhibitory effects on several immune effector cell types including NK cells 18,19 and CD4 + T cells 76,77 directly, 21 or via inhibition of DC function 20 or induction of regulatory T cell development 78 . In addition, antibody-mediated processes such as complement mediated lysis and antibody-dependent cell-mediated cytotoxicity can also be affected by MDSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Although CD8 + T cells are important in tumor clearance, they are not the only cell involved 75 . MDSCs have been reported to have inhibitory effects on several immune effector cell types including NK cells 18,19 and CD4 + T cells 76,77 directly, 21 or via inhibition of DC function 20 or induction of regulatory T cell development 78 . In addition, antibody-mediated processes such as complement mediated lysis and antibody-dependent cell-mediated cytotoxicity can also be affected by MDSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor size is expressed as tumor index, which is the square root of (length  width) as described previously (7). In the pulmonary metastatic model, mice were intravenously injected with 5  10 5 OVA/firefly luciferase-expressing melanoma, MO4-Luc (7).…”
Section: Tumor Inoculation and Antibody Treatmentmentioning
confidence: 99%
“…While the induction of tumor-specific CD8 þ T cells has been the main focus in cancer immunotherapy, recent studies have suggested that the better prognosis is correlated with higher levels of IFNg-expressing CD4 þ T (Th1) cells in patients with cancer, implying an important role of Th1 cells in controlling tumor regression (3)(4)(5). However, Th1 responses tend to be abolished in patients with cancer (3,5) and tumor-bearing animals (6,7). An induction of tolerance against immunosurveillance in tumor microenvironment is suggested to be the cause for failure of tumor-specific T cells to eradicate malignant cells (1,3,6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myeloid-derived suppressor cells secrete IL-10, IL-6, TNF-Alfa, IL-1 beta, COX-2, IFN-Gama,HIF-1 Alfa and ROS, skew the CD4+ T Cells to Tregs and suppress the antitumour immunity of CD4+, CD8+, and NK cells, resulting in the suppressive and tolerogenic environment and M2 phenotypic polarisation of tumour-associated macrophages favouring tumour progression. MDSC mediated cellular proliferation, angiogenesis by activation of STAT-3, invasion by MMP through degradation of the extracellular matrix or basement membrane and epithelial to mesenchymal transition by secretion of TGF-Beta, HGF, and FGF [16, 17, 27, 28]. …”
Section: Inflammatory Mediators Which Promote the Progression Of Cancmentioning
confidence: 99%